Fight like hell : the testimony of Mother Jones [videorecording (DVD)] - Lee, Kaiulani (Bullfrog Films, 2023)
Mother Jones, a fiery orator and fearless organizer for workers' rights, known as "the protector of children," and "the miners' angel," in a riveting performance by Kaiulani Lee.